Effect of microbiological inoculants DN‐1 on lignocellulose degradation during co‐composting of cattle manure with rice straw monitored by FTIR and SEM. Issue 2 (9th August 2015) - Xu, Jie; Xu, Xiuhong; Liu, Yue; Li, Hongtao; Liu, Huajing
Abstract : Lignocellulose is the uppermost limiting factor influencing the maturity process of agricultural waste compost. The purpose of this study was to determine the promotion of lignocellulose degradation by the inoculants DN‐1 during co‐composting of cattle manure with rice straw. Lignocellulose content, functional groups, and microscopic structure were investigated by the chemical determination, the Fourier transform infrared spectroscopy (FTIR) analysis, and the scanning electron microscopy (SEM) observation, respectively. The chemical determination indicated that the inoculants DN‐1 promoted the degradation of cellulose and hemicellulose in the initial stage of composting and the degradation of lignin in the later thermophilic stage. After composting, the degradation rate of cellulose, hemicelluloses, and lignin in the inoculated compost was 62.57%, 67.14%, and 42.54% respectively, while those in the natural compost was only 31.27%, 47.57%, and 22.21%, respectively. During composting, in the inoculated compost, the characteristic absorption peaks of cellulose and hemicellulose (at 3312, 2930, 1050, and 895 cm −1 ) and lignin (at 1506 cm −1 ) decreased noticeably, while in natural compost, except for the peak at 1050 cm −1, no obvious changes in these peaks were observed, confirming that the inoculants were effective in promoting the degradation of lignocellulose. The SEM images provided clear morphological evidence of lignocellulose degradation during composting. After composting, the serious degradation of parenchyma tissue (which is composed of cellulose and hemicellulose mainly) and sclerenchyma tissue (which is composed of lignin mainly) was observed in the inoculated compost. While in the natural compost, only the partial degradation of parenchyma tissue occurred, no obvious degradation of sclerenchyma tissue was found at the end of composting. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 345–351, 2016